Surface Metrology Principles for Snow and Ice Friction Studies - Brown, Christopher A. (Frontiers in Mechanical Engineering, 2021)
Recent advances in surface metrology science are applied to understanding friction with snow and ice. Conventional surface metrology’s measurement, analyses, and characterizations, have inherent limitations for elucidating tribological interactions. Strong functional correlations and confident discriminations with slider surface topographies, textures, or “roughness”, have largely eluded researchers using conventional methods. Building on 4 decades of research using multiscale geometric methods, two surface metrology axioms and corollaries are proposed with good potential to provide new technological insights.